AN EXPLORATION OF THE AGRO-TOWN IN THE ITALIAN COUNTRYSIDE AND RURAL DISTRICT - N. Galluzzo (Trakia Journal of Sciences)
The primary sector has been completely reshaped by the assignation of specific functions to farmers over the last 25 years, since legislators noted the importance of quality food productions to the rural and agroindustrial sectors and formally established rural and agri-food districts as legal entities. Agro-towns and rural districts in Italy, despite their peculiarities, represent an element of continuity in the path of social and economic development of the Italian countryside, contrasting the risk of marginalisation in rural areas through a propulsive growth of social capital and human interactions. The main purpose of this research was to assess the development of rural districts in some Italian regions as a consequence of the diffusion of agrotowns. The method of investigation has been a theoretical approach aimed at assessing the diffusion of the rural districts from 2016 to 2019 and by a comparison among Italian regions using some maps. Drawing some final remarks, agro-towns represent a fundamental pillar for the growth of the rural district in Italy due to their specificities in terms of social capital and local development, which are able to give a special connotation to the surrounding rural territory in a process of economic growth. In conclusion, the model of the rural district represents a spearhead for the countryside, emphasising all the peculiarities of rural areas where the impact of agro-towns has been significant in the past. The main consequence has been a transition of agrotowns from being degraded structures, where the incidence of agricultural underemployment was high, to structures where, despite the diffusion of large estates, there is an advanced social and economic development able to create a cohesive space that works to contrast the marginalisation of the Italian countryside.